Določanje ohranitvenih stanj kvalifikacijskih habitatnih tipov in vrst z metodo, ki temelji na mehki logiki - Grošelj, Petra (Gozdarski vestnik, 2015)
In the paper the mathematical model evaluating conservation status of forest habitats and habitats of the species is presented. The model is based on fuzzy logic and indicators are joined by inference rules. First empirical values of indicators are transformed into linguistic variables poor, acceptable and favorable and their membership functions are defined. Then inference rules between linguistic variables and final output are defined. The final result is expressed with number and linguistic value. The model was developed for conservation status of forest habitat types. Use of the model was shown for the forest management plan of forest management unit Snežnik and for conservation status of saproxylic beetles, for which the use was shown for the forest management plan Trnovo.
Keywords: ohranitveno stanje; mehka logika; logična pravila sklepanje; gozdni habitati; habitatne vrste; modeliranje